Two-Instant Reallocation in Two-Echelon Spare Parts Inventory Systems - SONG, Huawei (Institutional Knowledge at Singapore Management University, 2006)
In this paper, we study the problem of deciding when and how to perform reallocation of existing spare parts in a multi-echelon reparable item inventory system. We present a mathematical model that solves the problem when there are two reallocation instants, in response to the open challenge post by Cao and Silver(2005) to consider two or more possible reallocations within a replenishment cycle.